A Fast and Validated HPLC Method for Simultaneous Determination of Dopamine, Dobutamine, Phentolamine, Furosemide, and Aminophylline in Infusion Samples and Injection Formulations - Fuchao Chen; Baoxia Fang; Sicen Wang (Journal of Analytical Methods in Chemistry)
A simple, fast, and validated HPLC method was developed for the simultaneous quantization of five cardiovascular agents: dopamine (DPM), dobutamine (DBM), phentolamine (PTM), furosemide (FSM), and aminophylline (APL) either in infusion samples or in an injection dosage form. The proposed method was achieved with a 150 mm × 4.6 mm, 5.0 μm C18 column, by using a simple linear gradient. Mobile phase A was buffer (50 mM KH2PO4) and mobile Phase B was acetonitrile at a flow rate of 1.0 mL/min. The column temperature was kept at 30°C, and the injection volume was 20 μL. All analytes were separated simultaneously at a retention time (tr) of 3.93, 5.84, 7.06, 8.76, and 9.67 min for DPM, DBM, PTM, FSM, and APL, respectively, with a total run time of less than 15.0 min. The proposed method was validated according to ICH guidelines with respect to accuracy, precision, linearity, limit of detection, limit of quantitation, and robustness. Linearity was obtained over a concentration range of 12.0–240.0, 12.0–240.0, 20.0–200.0, 6.0–240.0, and 10.0–200.0 μg/mL DPM, DBM, PTM, FSM, and APL, respectively. Interday and intraday accuracy and precision data were recorded in the acceptable limits. The new method has successfully been applied for quantification of all five drugs in their injection dosage form, infusion samples, and for evaluation of the stability of investigated drugs in mixtures for endovenous use. The results of the stability study showed that mixtures of DPM, DBM, PTM, FSM, and APL in 5% glucose or 0.9% sodium chloride injection were stable for 48 hours when stored in polypropylene syringes at 25°C.